Topology and function of translocated EspZ - Nir Haritan; Etan Amse Bouman; Ipsita Nandi; Raisa Shtuhin-Rahav; Efrat Zlotkin-Rivkin; Tsafi Danieli; Naomi Melamed-Book; Yael Nir-Keren; Benjamin Aroeti (mBio, 2023)
ABSTRACT EspZ and Tir are essential virulence effectors of enteropathogenic Escherichia coli (EPEC). EspZ, the second translocated effector, has been suggested to antagonize host cell death induced by the first translocated effector, Tir (translocated intimin receptor). Another characteristic of EspZ is its localization to host mitochondria. However, studies that explored the mitochondrial localization of EspZ have examined the ectopically expressed effector and not the more physiologically relevant translocated effector. Here, we confirmed the membrane topology of translocated EspZ at infection sites and the involvement of Tir in confining its localization to these sites. Unlike the ectopically expressed EspZ, the translocated EspZ did not colocalize with mitochondrial markers. Moreover, no correlation has been found between the capacity of ectopically expressed EspZ to target mitochondria and the ability of translocated EspZ to protect against cell death. Translocated EspZ may have to some extent diminished F-actin pedestal formation induced by Tir but has a marked effect on protecting against host cell death and on promoting host colonization by the bacteria. Taken together, our results suggest that EspZ plays an essential role in facilitating bacterial colonization, likely by antagonizing cell death mediated by Tir at the onset of bacterial infection. This activity of EspZ, which occurs by targeting host membrane components at infection sites, and not mitochondria, may contribute to successful bacterial colonization of the infected intestine. IMPORTANCE EPEC is an important human pathogen that causes acute infantile diarrhea. EspZ is an essential virulence effector protein translocated from the bacterium into the host cells. Detailed knowledge of its mechanisms of action is, therefore, critical for better understanding the EPEC disease. We show that Tir, the first translocated effector, confines the localization of EspZ, the second translocated effector, to infection sites. This activity is important for antagonizing the pro-cell death activity conferred by Tir. Moreover, we show that translocated EspZ leads to effective bacterial colonization of the host. Hence, our data suggest that translocated EspZ is essential because it confers host cell survival to allow bacterial colonization at an early stage of bacterial infection. It performs these activities by targeting host membrane components at infection sites. Identifying these targets is critical for elucidating the molecular mechanism underlying the EspZ activity and the EPEC disease.